A Study of Environmental awareness among the students at Shaqra University and its relationship with sustainable development - Kamel, Laila Hanafy (Journal of agricultural, environmental and veterinary sciences, 2020)
The current study focused on measuring environmental awareness and its relationship to the variables of specialization and age, on the one hand, and its relationship to sustainable development among Shaqra University students in Shaqra in the second semester of the year 2018/2019 where the research community included three colleges, namely the College of Education, the College of Sciences and Humanities and the College of Applied Medical Sciences, In order to achieve the research objectives, the choice was made on the scale of environmental awareness that was used by (Al- Badrani, 2004), citing (Al- Dakhil, 2000), which consists of two axes, the first axis concerns environmental information and the second axis is concerned with the attitude towards the environment and adjustments were made to be ready for implementation as was the Confirmed the validity and reliability of the scale appropriate ways. The sample of the study was 110 female students, who were selected from the control sample Fourth level female students, the results of the research showed that the level of environmental awareness among the three college students is lower than the default test, 70% of the degree of the questionnaire, where the average awareness of the students reached 58.32%.The results also showed an inverse relationship between environmental information and behavior towards the environment. Statistical significance according to the speciality or age variable at the level of indication α= 0.05 The research also showed a strong correlation between environmentalawareness and the information of female students on sustainable development of the environment at the level of significance α= 0. 01 and a number of recommendations were made that aim to raise the level of environmental awareness for students and activate the diffusion of green culture to protect the environment.
Keywords: The environmental awareness; Sustainable Development; Green culture